1995
DOI: 10.1016/s0741-5214(95)70289-x
|View full text |Cite
|
Sign up to set email alerts
|

Venous duplex imaging follow-up of acute symptomatic deep vein thrombosis of the leg

Abstract: Rates of resolution of DVT were similar for the different veins of the leg studied. There was a high proportion of unstable thrombi, which present a high potential risk of embolization. Serial duplex scanning after DVT renders important information with regard to thrombus resolution, propagation, and attachment to the vein wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 17 publications
2
40
0
Order By: Relevance
“…In a prospective study of 69 patients with deep venous thrombosis, Caprini et al 9 found no significant difference in thrombosis regression between venous segments (common femoral, superficial femoral, popliteal, and calf veins). In contrast, we found a significant difference between iliac and infra-inguinal deep venous thromboses: iliac vein thrombi exhibited a lesser and slower regression.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a prospective study of 69 patients with deep venous thrombosis, Caprini et al 9 found no significant difference in thrombosis regression between venous segments (common femoral, superficial femoral, popliteal, and calf veins). In contrast, we found a significant difference between iliac and infra-inguinal deep venous thromboses: iliac vein thrombi exhibited a lesser and slower regression.…”
Section: Discussionmentioning
confidence: 96%
“…[1][2][3][4][5][8][9][10][11][12][13][14] Like Ramshorst et al, 8 we used a semiquantitative index for both initial and followup scoring of the thrombosis. Ramshorst et al studied 80 thrombosed venous segments, 49 of which involved the popliteal and femoral veins.…”
Section: Discussionmentioning
confidence: 99%
“…Because thrombosis can induce inflammation and subsequently might lead to hypertrophy of the surrounding vessel wall, the distensibility of a thrombotic vein is reduced by it, causing pain in patients while stretching 5) . A thrombus blocks venous return leading to edema.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, FFT in the proximal vein would have few clinical findings. According to previous studies, after thrombolytic therapy, 9.2-10.7 days are required for FFT to attach to the venous wall 5,10) . These reports suggest that early ambulation (within 10 days after surgery), which is recommended in clinical settings, presents a risk of PE if patients have FFT.…”
Section: Discussionmentioning
confidence: 99%
“…However, almost every artery crossing a vein in the pelvic area can produce a compression, but only left-sided iliofemoral DVT is clearly more prevalent in comparison with DVT on the right side (at least three-fold more frequent). In addition, iliofemoral DVT gives poor spontaneous recanalisation (only 30% of cases), whereas as many as 70% of femoral DVT will recanalise [9,10]. This is of particular importance regarding the risk of development and severity of post-thrombotic syndrome.…”
Section: May-thurner Syndromementioning
confidence: 99%